Changes in the Serum Protein Electrophoresis Profile in Dogs With Pyometra - Yoon, Ji-Seon; Yu, DoHyeon; Park, Jinho (Frontiers in Veterinary Science, 2021)
Serum proteins are involved in the regulation of inflammation, and therefore, serum protein profiling provides important insights in diverse inflammatory reactions. Accordingly, concentrations of single APPs, such as the C-reactive protein (CRP), serum amyloid A (SAA), and haptoglobin (Hp), have been described as indicators of inflammatory response in canine pyometra. However, there is little information regarding the overall serum protein profile obtained by SPE in canine pyometra. The present study was thus aimed to identify changes in the serum protein profile to monitor inflammation in dogs with pyometra using serum protein electrophoresis (SPE), in addition to the analysis of the concentration of single acute phase proteins (APPs). By SPE analysis, decreased levels of albumin and elevated levels of α2-globulin and β-globulin were noted in dogs with pyometra. In addition, the concentration of APPs, including the C-reactive protein (CRP), serum amyloid A (SAA), and haptoglobin (Hp), were also elevated in dogs with pyometra. The present study provides fundamental data for inflammatory indicators of canine pyometra.